-11+10x(p+10)=4-5(2p+11)

Simple and best practice solution for -11+10x(p+10)=4-5(2p+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11+10x(p+10)=4-5(2p+11) equation:


Simplifying
-11 + 10x(p + 10) = 4 + -5(2p + 11)

Reorder the terms:
-11 + 10x(10 + p) = 4 + -5(2p + 11)
-11 + (10 * 10x + p * 10x) = 4 + -5(2p + 11)

Reorder the terms:
-11 + (10px + 100x) = 4 + -5(2p + 11)
-11 + (10px + 100x) = 4 + -5(2p + 11)

Reorder the terms:
-11 + 10px + 100x = 4 + -5(11 + 2p)
-11 + 10px + 100x = 4 + (11 * -5 + 2p * -5)
-11 + 10px + 100x = 4 + (-55 + -10p)

Combine like terms: 4 + -55 = -51
-11 + 10px + 100x = -51 + -10p

Solving
-11 + 10px + 100x = -51 + -10p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '10p' to each side of the equation.
-11 + 10px + 10p + 100x = -51 + -10p + 10p

Reorder the terms:
-11 + 10p + 10px + 100x = -51 + -10p + 10p

Combine like terms: -10p + 10p = 0
-11 + 10p + 10px + 100x = -51 + 0
-11 + 10p + 10px + 100x = -51

Add '11' to each side of the equation.
-11 + 10p + 10px + 11 + 100x = -51 + 11

Reorder the terms:
-11 + 11 + 10p + 10px + 100x = -51 + 11

Combine like terms: -11 + 11 = 0
0 + 10p + 10px + 100x = -51 + 11
10p + 10px + 100x = -51 + 11

Combine like terms: -51 + 11 = -40
10p + 10px + 100x = -40

Add '-100x' to each side of the equation.
10p + 10px + 100x + -100x = -40 + -100x

Combine like terms: 100x + -100x = 0
10p + 10px + 0 = -40 + -100x
10p + 10px = -40 + -100x

Reorder the terms:
40 + 10p + 10px + 100x = -40 + -100x + 40 + 100x

Reorder the terms:
40 + 10p + 10px + 100x = -40 + 40 + -100x + 100x

Combine like terms: -40 + 40 = 0
40 + 10p + 10px + 100x = 0 + -100x + 100x
40 + 10p + 10px + 100x = -100x + 100x

Combine like terms: -100x + 100x = 0
40 + 10p + 10px + 100x = 0

Factor out the Greatest Common Factor (GCF), '10'.
10(4 + p + px + 10x) = 0

Ignore the factor 10.

Subproblem 1

Set the factor '(4 + p + px + 10x)' equal to zero and attempt to solve: Simplifying 4 + p + px + 10x = 0 Solving 4 + p + px + 10x = 0 Move all terms containing p to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + p + px + -4 + 10x = 0 + -4 Reorder the terms: 4 + -4 + p + px + 10x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + p + px + 10x = 0 + -4 p + px + 10x = 0 + -4 Combine like terms: 0 + -4 = -4 p + px + 10x = -4 Add '-10x' to each side of the equation. p + px + 10x + -10x = -4 + -10x Combine like terms: 10x + -10x = 0 p + px + 0 = -4 + -10x p + px = -4 + -10x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 20-2x=-4+4x | | 37-7x=10+2x | | (10x^2-7x-2)-(3x^2-4x+6)= | | 1/2x-3/10 | | (3u)(2y^4)(7u^8y^3)= | | -1x=-27 | | 4xy^-2/12x^-1/3y-5 | | (-1/3*e^(-x^2/6)*x)*(9x^2-x^4/3) | | 5m-2(m+2)=-2-15 | | 16y-x^4=0 | | X-3=4+7 | | 2/3y-3=9 | | 1+X+2=2+3 | | 2X=1+4 | | 9x9/15 | | X-2+3=6+5 | | v+(v+6)=30 | | 2x+5-3x=-1 | | X=-0.9 | | 6.1=-3.5+6v | | 72=-1.33x | | 72=-1.33 | | 3(5x-3)+2(14-2x)-2(5x+2)=-1 | | 8-(-3x)=x | | 11=5y+-3y | | -1.1-(-10.1)= | | (6y+8)-(3+5y)=8 | | 400x= | | 15+h=10 | | 3(8)=n(0.08)(300) | | 8x+4=x-14 | | 13x^3-36x=-12x^2 |

Equations solver categories